Impact of content and length of curauá fibers on mechanical behavior of extruded cementitious composites: Analysis of variance - Teixeira, R. S.; Santos, S. F. [UNESP]; Christoforo, A. L.; Payá, J.; Savastano, H.; Lahr, F.A. Rocco (Elsevier, 2019)
The use of composite materials in construction has grown considerably in recent years, such as cementitious matrices and concrete reinforced with fibers. The vegetable fibers have become an alternative due to its abundance, low cost and low energy consumption for its production, and appropriate properties mechanical. Curauá fiber is a plant native from Amazonas harvested manually in commercial farming and it is used in the manufacture of ropes and baskets or as reinforcement in composite with organic matrix of components for cars, buses and trucks. On the other hand, the extrusion process can produce composites with high-density matrix with fibers, low permeability and good interface between fiber and matrix. This process is also compatible with the use of vegetable fibers as raw materials in the production of cost-effective construction elements such as ceiling panels and drywalls. The objective of this research was use the analysis of variance (ANOVA)for evaluating with rigor mathematical the influence of content and length of curauá fibers on the mechanical behavior of the extruded cementitious composites. Composites without fibers and reinforced with 1% and 2% by mass of fibers as well as 6 mm and 10 mm of length these curauá fibers were evaluated. The composites with fibers of 10 mm have showed better mechanical results. Besides, the composites with fibers curauá after 200 accelerated aging cycles were better than one non-aging.
Keywords: Amazonian fiber; Extrusion process; Lignocellulosic fiber; Mechanical of fracture